2021
DOI: 10.1002/car.2709
|View full text |Cite
|
Sign up to set email alerts
|

Child Sexual Exploitation: A Survey of Knowledge and Confidence of Healthcare Providers in Saskatchewan, Canada

Abstract: Many human trafficking victims access healthcare, but most are not identified.• Healthcare providers' overall knowledge in identifying commercially sexually exploited children was strong.• Healthcare providers lack confidence in identifying and managing sexually exploited children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 21 publications
(22 reference statements)
0
2
0
Order By: Relevance
“…For example, although educational and medical societies recommend that students learn to recognize and provide care for sexually trafficked individuals, Talbott and colleagues [ 41 ] were able to identify only four programs which aimed to train medical students on identification and intervention. A Canadian study of medical professionals ( n = 125) found that 40% of physicians and 51% of other health professionals (e.g., nurses and psychologists) had never received training related to CST and did not feel comfortable making identification judgments [ 42 •]. Further some research suggests that healthcare providers may be more attuned to general signs of child maltreatment rather than having specific knowledge regarding risks of CST [ 42 •, 43 ].…”
Section: Identification and Interventionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, although educational and medical societies recommend that students learn to recognize and provide care for sexually trafficked individuals, Talbott and colleagues [ 41 ] were able to identify only four programs which aimed to train medical students on identification and intervention. A Canadian study of medical professionals ( n = 125) found that 40% of physicians and 51% of other health professionals (e.g., nurses and psychologists) had never received training related to CST and did not feel comfortable making identification judgments [ 42 •]. Further some research suggests that healthcare providers may be more attuned to general signs of child maltreatment rather than having specific knowledge regarding risks of CST [ 42 •, 43 ].…”
Section: Identification and Interventionmentioning
confidence: 99%
“…A Canadian study of medical professionals ( n = 125) found that 40% of physicians and 51% of other health professionals (e.g., nurses and psychologists) had never received training related to CST and did not feel comfortable making identification judgments [ 42 •]. Further some research suggests that healthcare providers may be more attuned to general signs of child maltreatment rather than having specific knowledge regarding risks of CST [ 42 •, 43 ].…”
Section: Identification and Interventionmentioning
confidence: 99%